2011
DOI: 10.1016/j.juro.2010.12.103
|View full text |Cite
|
Sign up to set email alerts
|

Two-Sided Bulbar Urethroplasty Using Dorsal Plus Ventral Oral Graft: Urinary and Sexual Outcomes of a New Technique

Abstract: In cases of tight bulbar stricture the dorsal plus ventral buccal mucosa graft provides adequate urethral augmentation by preserving the urethral plate and avoiding postoperative sexual complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…This technique preserves the remaining urethral plate and avoids the use of a wide single dorsal or ventral graft. In this report, there was no deterioration in erectile function after surgery in all 49 of 73 patients who were pre-operatively sexually active (Palminteri et al, 2011).…”
Section: Anterior Urethroplastymentioning
confidence: 43%
“…This technique preserves the remaining urethral plate and avoids the use of a wide single dorsal or ventral graft. In this report, there was no deterioration in erectile function after surgery in all 49 of 73 patients who were pre-operatively sexually active (Palminteri et al, 2011).…”
Section: Anterior Urethroplastymentioning
confidence: 43%
“…Berglund and Angermeier proved that the combination of a buccal mucosa graft and penile or scrotal skin flap is a reliable and durable method of single‐stage repair for extensive urethral stricture disease . Several authors reported simultaneous use of two buccal mucosa grafts for circumferential urethral replacement . Similarly, Chen et al .…”
Section: Discussionmentioning
confidence: 98%
“…Palminteri et al reported an 88% success rate in 73 patients with bulbar strictures undergoing OBMGU. 39 In an expanded assessment of OBMGU, a recent multi-institutional analysis of 36 patients validated these promising results for strictures along the entire anterior urethra with an 89% success rate following a mean of 16 months after urethroplasty. 10 Gelman et al described a similar version of OBMGU through a dorsal approach, thus preserving the ventral corpus spongiosum.…”
Section: Overlapping Dorsal and Ventral Buccal Graftingmentioning
confidence: 89%
“…The OBMGU concept allows use of more narrow ventral grafts, and thus less likelihood of sacculation. 10,39 Importantly, this technique avoids tubularized grafts and urethral transection. Palminteri et al reported an 88% success rate in 73 patients with bulbar strictures undergoing OBMGU.…”
Section: Overlapping Dorsal and Ventral Buccal Graftingmentioning
confidence: 99%